Institutional Provision of Tutorial Support Services - A prerequisite in Influencing Learner Participation in Distance Learning Programmes: The Case of Distance Learning Students Undertaking Diploma Course in Selected Distance Training Centers of the Coll - Evariste, Gahima; Omondi , Bowa; Kithung'A, Peter (International Journal of Online and Distance Learning, 2022)
Purpose: The purpose was to assess the influence of the provision of tutorial support services on learner participation in distance learning programmes in the College of Education, University of Rwanda. The objectives were to establish the extent to which scheduling of tutorial meetings for face-to-face classes influence learner participation in distance learning programmes: assess whether provision of career guidance and counselling services influence learner participation in distance learning programmes; establish the extent to which scheduling of workshops and seminars influence learner participation in distance learning programmes; assess whether scheduling of peers meeting for discussion and interaction influence learner participation in distance learning programmes and to establish the extent to which library services influence learner participation in distance learning programmes. Methodology: The methodology utilized both quantitative and qualitative approaches and embraced by a cross- sectional study design which was employed to collect data from the six selected Distance learning centers in the college of Education. A sample study comprised of 315 students out of 1,474 that formed the target population. Findings: Findings showed that provision of tutorial support services positively and significantly influence learner participation in the distance learning as indicated by regression coefficient of Î²= 270.222 t= 6389, p= 0.000 <0.05). Therefore, the null hypothesis H: was rejected and the alternative (Hâ‚) was accepted that provision of tutorial support services have no significant effect on learner participation in the distance learning in the College of Education. Even though, findings from the study provide a strong indication that learner participation is influenced by tutorial support services such as scheduling of tutorial meeting face-to-face classes, provision of career guidance and counselling services, scheduling of the workshops and seminars, scheduling of peers meeting for discussion and interaction and library services, they are inadequate. In addition, the study did not find scheduling of workshops and seminars, as well as provision of career guidance and counselling services indicators to be statistically significant. Unique Contribution to Theory, Practice and Policy: The unique contribution for this study in practice is that the University of Rwanda should lay down practical strategies of providing the necessary support services to learners and ensuring that digital technologies are enhanced to enable them to effectively and efficiently participate through discussions and interactions amongst themselves. In theory, this study will open up new room for academic discussions in the pedagogic perspectives and to policy imperatives, the government should find funding mechanisms on what works well for the successful delivery of distance learning programmes.